2020
DOI: 10.1101/2020.02.12.946749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intracellular Lipid Droplet Accumulation Occurs Early Following Viral Infection and Is Required for an Efficient Interferon Response

Abstract: 27Lipid droplets (LDs) are increasingly recognized as critical organelles in signalling events, 28 transient protein sequestration and inter-organelle interactions. However, the role LDs play in 29 antiviral innate immune pathways remains unknown. Here we demonstrate that induction of 30 LDs occurs as early as 2 hours post viral infection, is transient, and returns to basal levels by 31 72 hours. This phenomenon occurred following viral infections, both in vitro and in vivo. 32 Virally driven LD induc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…To examine LD motility dynamics in the context of the activation of early innate immune pathways, we first developed a pipeline to image and track LDs in live primary immortalised astrocyte cells. Astrocytes were chosen as a model cell type, because they are known to alter LD numbers following viral stimulation and infection, and have a high number of basal LDs [ 21 ]. Additionally, astrocytes are known to be rapid producers of an effective antiviral response [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To examine LD motility dynamics in the context of the activation of early innate immune pathways, we first developed a pipeline to image and track LDs in live primary immortalised astrocyte cells. Astrocytes were chosen as a model cell type, because they are known to alter LD numbers following viral stimulation and infection, and have a high number of basal LDs [ 21 ]. Additionally, astrocytes are known to be rapid producers of an effective antiviral response [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…During viral infection, LDs have been demonstrated to be redistributed within the cell, and this has been hypothesised to be associated with viral host cell rearrangement, in order to facilitate a more effective viral life cycle [ 19 , 20 ]. However, it has recently been demonstrated that LDs are upregulated very early following both viral and bacterial infection, likely prior to pathogen replication [ 21 ] (reviewed in [ 22 ]). The dynamics such as speed and displacement of LDs remains unstudied in the context of very early viral infection; here, we demonstrate that LD dynamics significantly change following the activation of antiviral innate immune receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the question as to the role of the LD in innate immune recognition of viral infection. It is emerging that the LD can act as a hub for signaling and we have recently shown that LDs influence the efficiency of the early innate response after viral infection ( Monson et al, 2018 , 2020 Preprint ). One could envisage that the LD may not be essential for MAVS-dependent signaling from the mitochondria but may be important for MAVS-dependent signaling from peroxisomes.…”
Section: Discussionmentioning
confidence: 99%